The Influence of Process Speed and Credit Costs on UMKM Credit Customer Loyalty at BRI Unit Balongpanggang with Customer Satisfaction as an Intervening Variable - Wibowo K, Febri Susanto; Rosyid, Amrun; Asa, Cita Sophia (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study aims to analyse the direct and indirect effects of process speed and credit cost on customer loyalty of MSME credit customers at Bank Rakyat Indonesia (BRI) Unit Balongpanggang, with customer satisfaction as an intervening variable. Design/methodology/approach: This research employs a quantitative approach using primary data collected through questionnaires distributed to MSME credit customers. The sampling technique used purposive sampling. Data were analysed using multiple linear regression and path analysis to examine both direct and indirect relationships among variables. Findings: The results indicate that process speed and credit cost significantly influence customer satisfaction. Process speed significantly affects customer loyalty, while credit cost influences loyalty indirectly through satisfaction. Customer satisfaction has a significant positive effect on loyalty and mediates the relationship between the independent variables and loyalty. Research limitations/implications: This study is limited to MSME credit customers at BRI Unit Balongpanggang and uses cross-sectional data, which may not capture changes over time. Practical implications: The findings suggest that banks should improve credit processing efficiency and maintain competitive credit costs to enhance satisfaction and long-term customer loyalty. Originality/value: This study offers a contextual model integrating process speed and credit cost simultaneously in explaining MSME credit customer loyalty through satisfaction in the banking sector. Paper type: Research paper